It's snowing! It's snowing! - Prelutsky, Jack.; Titherington, Jeanne (New York : Greenwillow Books, 1984)
A collection of more than a dozen poems that capture the excitement of winter.
3.0
K-3
Keywords: Winter -- Juvenile poetry; Snow -- Juvenile poetry; Children's poetry, American; Winter -- Poetry; Snow -- Poetry; American poetry; Winter -- Poetry; Snow -- Poetry; American poetry